Functional and radiological outcomes of thoracolumbar traumatic spine fractures managed conservatively according to Thoracolumbar Injury Severity Score - Bagga, Rajdeep Singh (J Craniovertebr Junction Spine, 2017)
AIM: To study the functional and radiological outcomes in cases managed conservatively for single-level traumatic thoracolumbar spine fractures without neurological deficit. MATERIALS AND METHODS: In this prospective study design, thirty patients who presented to tertiary care hospital and diagnosed with posttraumatic thoracolumbar vertebral fracture without any neurodeficit were recruited. All the patients were managed conservatively as per the protocol which included bed rest, spinal braces, and physiotherapy. Adequate analgesia was given wherever necessary. The patients were followed at regular intervals up to a maximum of 2 years. Clinically visual analog scale (VAS) score and Roland Morris Disability Questionnaire (RMDQ)-24 were assessed and radiologically local vertebral kyphosis, scoliosis, and loss of body height were noted at each follow-up. RESULTS: The data was statistically analyzed and the results were as follows. Thoracolumbar fractures were more in young adults (<26 years) and more so among the males (80% cases). The most common fracture type in our study was compression fracture. The most common site involved in our study was L1 vertebra (36.7%). There was a significant decrease of VAS score (pain score) in 79% cases with the maximum decrease in type A1 fracture. The mean RMDQ-4 score in our study was 5.53. The overall progression of kyphosis was 1.9°. There was no relation found between the kyphotic deformity and the clinical outcomes (VAS and RMDQ-24 scores). Canal size changes were found to be insignificant at the end of 2 years compared to baseline. CONCLUSION: Study showed favorable outcomes in terms of return to daily activities, making it a good option in managing Type A1 dorsolumbar fractures. Though there was a progression of kyphosis but no neurological deficit was seen.